Hindu Perspectives on the Thirst for Transcendence - Raman, Varadaraja V. (Zygon, 2003)
Abstract. Definitions of nature and transcendence are given, and the framework of Hindu thought is presented. The levels of reality as discovered by physics are then discussed, which leads us to revise our notions of reality and objectivity. Transcendence is defined as something beyond matter-energy in space-time and is explored in several contexts of modern science, as in pre-Big-Bang state, negative entropy, information, complexity, and others. Finally, a philosophical reflection on consciousness is presented.